1989
DOI: 10.1139/x89-206
|View full text |Cite
|
Sign up to set email alerts
|

Production of clonal plantlets of tropical pine in tissue culture via axillary shoot activation

Abstract: A method for the production of multiple clonal plantlets of Pinuscaribaea var. hondurensis Morlet, P. oocarpa Schiede, and P. tecunumanii Equiluz and Perry (P. patula Schiede and Deppe ssp. tecunumanii (Equiluz and Perry) Styles) from juvenile sources is described. The procedure is based on the spontaneous production of axillary shoots following shoot elongation. Much interclonal variation exists with respect to expiant multiplication. The addition of activated charcoal (0.1%) stimulates shoot elongation, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The micropropagation of P. caribaea using different media and methods was previously reported (Webb & Santiago 1983;Berlyn et al 1987;Skidmore et al 1988;Baxter et al 1989). These studies showed that benzyladenine is necessary in the induction of adventitious shoots.…”
Section: Introductionmentioning
confidence: 94%
“…The micropropagation of P. caribaea using different media and methods was previously reported (Webb & Santiago 1983;Berlyn et al 1987;Skidmore et al 1988;Baxter et al 1989). These studies showed that benzyladenine is necessary in the induction of adventitious shoots.…”
Section: Introductionmentioning
confidence: 94%
“…After culturing for 4 weeks, axillary buds were actively flushed as shown in Fig.l. The flushed shoots were transferred directly into GD medium containing less than 1 btM naphthaleneacetic acid (NAA), for shooting of axillary buds, according to the method of Baxter et al (1989).…”
Section: Collection and Sterilization Of Explantsmentioning
confidence: 99%
“…Baxter et al (1989) obtained rooting in nonsterile conditions in a peat:perlite medium with daily misting under a sealed propagator.…”
Section: Rooting Of Adventitious Shootsmentioning
confidence: 99%
“…Rooting in conifers generally requires exogenous application of auxins (Mohammed & Vidaver 1988). However, Baxter et al (1989) rooted 55% of in vitro produced shoots of P. caribaea without auxin pretreatment and in nonsterile conditions. In this study, rooting in shoots not treated with auxins occurred at 24%, which did not significantly differ from those treated with 0.5p~M NAA (20%), l p~M NAA (48%), 100 I~M NAA (38%), 1 p~M NAA + 10 p~M IBA (15%), and 10 p~M IBA (18%).…”
Section: Rooting Of Adventitious Shootsmentioning
confidence: 99%
See 1 more Smart Citation